2018
DOI: 10.1002/tcr.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate‐Based Cathode Materials for Li‐ and Na‐Ion Batteries

Abstract: Electrochemical energy storage via Li-ion batteries has changed modern life drastically and has enabled technologies such as portable electronic devices, electric vehicles and stationary grid storage. However, with the steadfast technological evolution and increasing energy demands, batteries need to be constantly improved to meet the needs of our society. Furthermore, increasing concerns are raised regarding sustainability, availability of raw materials and cost. Therefore, extensive research efforts have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 75 publications
2
25
0
Order By: Relevance
“…1 Thanks to the high electronegativity of the sulfate groups, an inductive effect 2 raises the reduction potential of the Fe 3+ /Fe 2+ couple to ~ 3.8 V vs. Na + /Na 0 . This value of potential is the highest reported for the Fe 3+ /Fe 2+ couple 1,3 and is combined with a theoretical specific capacity of ~ 120 mAh/g if x = 0. 4 Unlike most A 2 M 2 (XO 4 ) 3 compounds, which crystallize in a NASICON structure, [5][6][7] NFS displays an alluaudite-type structure (Figure 1) with large channels favoring fast diffusion of sodium ions.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…1 Thanks to the high electronegativity of the sulfate groups, an inductive effect 2 raises the reduction potential of the Fe 3+ /Fe 2+ couple to ~ 3.8 V vs. Na + /Na 0 . This value of potential is the highest reported for the Fe 3+ /Fe 2+ couple 1,3 and is combined with a theoretical specific capacity of ~ 120 mAh/g if x = 0. 4 Unlike most A 2 M 2 (XO 4 ) 3 compounds, which crystallize in a NASICON structure, [5][6][7] NFS displays an alluaudite-type structure (Figure 1) with large channels favoring fast diffusion of sodium ions.…”
Section: Introductionsupporting
confidence: 60%
“…This value of potential is the highest reported for the Fe 3+ /Fe 2+ couple 1,3 and is combined with a theoretical specific capacity of ~ 120 mAh/g if x = 0. 4 Unlike most A 2 M 2 (XO 4 ) 3 compounds, which crystallize in a NASICON structure, [5][6][7] NFS displays an alluaudite-type structure (Figure 1) with large channels favoring fast diffusion of sodium ions. 1,4,5,[8][9][10][11] It was soon observed that, in practice, a sodium-rich Na 2+2x Fe 2-x (SO 4 ) 3 phase with x ≈ 0.25 was obtained instead of the stoichiometric compound Na 2 Fe 2 (SO 4 ) 3 4,12 .…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…[18][19][20][21] Vanadium sulfates are attractive candidate compounds and while the search for new crystal structures and compositions is ongoing, there are existing vanadium sulfates that can be explored. 18,22 V 2 O 3 (SO 4 ) 2 can accept four Li + ions, delivering a theoretical capacity of 313 mA h g À1 . Here, we study the Li + insertion into V 2 O 3 (SO 4 ) 2 using two methods (1) electrochemical lithiation and (2) chemical lithiation using n-butyllithium.…”
Section: àmentioning
confidence: 99%